Pengaruh Media Pembelajaran Dengan Audio Visual Terhadap Tingkat Kompetensi Mahasiswa Dalam Perekaman EKG - Sugiyarto Sugiyarto ((JKG) Jurnal Keperawatan Global, 2016)
Abstract: Audio Visual Learning, Competence, ECG Recording. This study aimed to determine the affect of audio-visual learning media to the level of students' competences of ECG recording. This research is a quantitative study with Quasy Experimental methods. The research design of this study used pre-test and post-test control group. The numbers of respondents were 44 nursing students of Poltekkes Surakarta. Dependent Test is used to pre-test and post-test in treatment groups and also pre-test and post-test in control group if data distributed normally, if not normal using Wilcoxon. Independent T tests is used to post-test in treatment and control group if data distributed normally, if not normal using Mann Whitney. Normality test data used Kolmogor-Smirnov. The P value of treatment and control groups, before and after the intervention, were similiar (0.000), P value <0.05. The conclusion of this study was audio-visual learning media has better effect on students' competences of ECG recording than using phantom media. So that, educators are expected to use audio-visual learning media as their learning media for students. Students are expected to have better skills in nursing services.